The Zaltman Metaphor Elicitation Technique (ZMET) in qualitative research: a systematic review of its use for exploring the subconscious mind - J. Seno Aditya Utama; Nurlaela Widyarini (Universitas Mercu Buana Yogyakarta, 2025)
The Zaltman Metaphor Elicitation Technique (ZMET) is a qualitative research method employed to elicit individuals' subconscious thoughts, feelings, and experiences by exploring metaphors. This systematic review, encompassing 47 studies published between 2019 and 2023, demonstrates that ZMET is frequently utilised within marketing and tourism, focusing primarily on perception, experience, and meaning. Principal findings indicate that the modifications to Storytelling and Missed Images are the most commonly implemented, whilst combinations with in-depth interviews and grounded theory are prevalent. Thematic analysis identified five principal themes: experience and emotion, meaning and perception, identity and self, values and beliefs, and decision-making. ZMET effectively investigated these themes, particularly within contexts involving complex emotions and experiences. This review concludes that ZMET remains a relevant and adaptable method within qualitative research. Its core strength lies in its capacity to uncover hidden layers of meaning, whilst its weaknesses pertain to analytical complexity and potential subjectivity. Implications and recommendations for best practice, including the necessity for meticulous planning, comprehensive interviewer training, and robust data triangulation, are also discussed concerning the future development and application of ZMET.